Penicillin Allergy De-labeling Results in Significant Changes in Outpatient Antibiotic Prescribing Patterns - Hills, Thomas; Arroll, Nicola; Duffy, Eamon; Capstick, Janice; Jordan, Anthony; Fitzharris, Penny (Frontiers in Allergy, 2020)
Unverified penicillin allergies are common but most patients with a penicillin allergy label can safely use penicillin antibiotics. Penicillin allergy labels are associated with poor clinical outcomes and overuse of second-line antibiotics. There is increasing focus on penicillin allergy ‘de-labelling’ as a tool to improve antibiotic prescribing and antimicrobial stewardship. The effect of outpatient penicillin allergy de-labelling on long-term antibiotic use is uncertain. We performed a retrospective pre- and post- study of antibiotic dispensing patterns, from an electronic dispensing data repository, in patients undergoing penicillin allergy assessment at Auckland City Hospital, New Zealand. Over a mean follow-up of 4.55 years, 215/304 (70.7%) of de-labelled patients were dispensed a penicillin antibiotic. Rates of penicillin antibiotic dispensing were 0.24 (0.18-0.30) penicillin courses per year before de-labelling and 0.80 (0.67-0.93) following de-labelling with a reduction in total antibiotic use from 2.30 (2.06-2.54) to 1.79 (1.59-1.99) antibiotic courses per year. In de-labelled patients, the proportion of antibiotic courses that were penicillin antibiotics increased from 12.81% to 39.62%. Rates of macrolide, cephalosporin, trimethoprim/co-trimoxazole, fluoroquinolone, ‘other’ non-penicillin antibiotic use, and broad-spectrum antibiotic use were all lower following de-labelling. Further, antibiotic costs were lower following de-labelling. In this study, penicillin allergy de-labelling was associated with significant changes in antibiotic dispensing patterns.